On the integration of the CAx systems towards sustainable production - Salonitis, Konstantinos; Stavropoulos, Panagiotis (Elsevier, 2013)
Achieving sustainable development and succeeding in sustainable production requires changes in industrial processes, type and quantity of resources used, treatment of waste, control of emissions, and finally in the final products. This paper describes a methodology of integrating CAD/CAPP/CAM systems, aiming at the development of methods and models for addressing the challenges arising within the process-planning phase and contributing to the continuous improvement initiatives within the production and manufacturing systems. The ultimate goal of such integration is to assess alternative process plans in different levels, through which, the utilization of the various available resources (such as hardware, personnel and even subcontractors) and their optimal setup can contribute in the overall sustainability of the production facilities.